RELEVANCE AND CHALLENGES OF IMPLEMENTING AUTHENTIC ASSESSMENT IN 21ST CENTURY LEARNING IN GLOBAL AND NATIONAL PERSPECTIVES - Syukri, Habib (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2024)
Learning in the 21st century very develop rapidly, along with with development of the era of globalization that leads to to the digital era. Along with with change era that, then world education is also facing a new era, namely the era of education that is directed on digitalization. In the era of rapidly developing globalization, education faces major challenges in preparing students to face the needs and demands of the 21st century. Learning in this century does not only focus on mastering theoretical knowledge, but also 21st century skills, such as critical thinking, creativity, collaboration, and communication ( 4C ). In response to these changes, the assessment models used in education also need to undergo a transformation. This is where the important role of authentic assessment, which aims to assess skills that are relevant to the real world, becomes increasingly important. Authentic assessment offers a more holistic approach by measuring students' ability to apply their knowledge in practical contexts, rather than simply testing memorization or theoretical understanding.